Novel methods for 18F-radiolabelling - Calderwood, S (2016)
The expansion of [18F]-radiolabelling methodologies is vital for the advancement of Positron Emission Tomography (PET) as a medical imaging tool. Novel protocols will simplify access to current PET tracers and allow development of original tracers, potentially enhancing the imaging quality or permit imaging of a wider range of clinical problems. A general introduction is presented in Chapter 1, covering PET, application of fluorine-19 in the pharmaceutical industry, the production of fluorine-18 and the current state-of -art for [18F]-radiolabelling. The results chapters are divided in to two parts; Part 1 (Chapters 2 - 4) concern the synthesis of [18F]fluoroarenes and Part II (Chapters 5 and 6) discuss diversity oriented radiofluorination techniques, targeting novel [18F]motifs. In Part I, Chapter 2 describes the use of hypervalent iodine reagents to meditate an umpolung approach for fluorination and radiofluorination of N-arylsulfonamides and anilides. Chapter 3 again utilises hypervalent iodine reagents, but as spirocyclic iodonium(III) ylide precursors, being applied to semi-automated and automated microfluidic conditions. Chapter 4 discusses the development of conditions for the production and isolation of radiopharmaceuticals employing Cu(II)-mediated radiofluorination of aryl boronic pinacol esters. In Part II, Chapter 5 discusses the applicability of halogen exchange reactions to reach polyfluorinated motfis and Chapter 6 focuses on the application of a single diazo precursor to access three polyfluorinated motifs with single-step reactions. Finally, Chapter 7 provides experimental data for compounds discussed in this thesis.